Die Vorgeschichte der ‚Brecht-Lukács-Debatte‘ - Peitsch, Helmut (2016)
Werner Mittenzwei’s article of 1967, the title of which coined the term “Brecht-Lukács-Debatte”, is widely considered as a milestone in the development of East German literary criticism towards an “emancipation” from party politics. By placing Mittenzwei’s contribution in the wider context of discussions about the literature of the GDR, within the SED and the writers’ union as well as at international conferences, this article attempts to trace the emergence of “Umfunktionierung” both as a key term and in its official approval by the party.
https://rightsstatements.org/vocab/InC/1.0/ ; info:eu-repo/semantics/openAccess
Keywords: Institut für Germanistik